Problematika dan Tantangan Santri di Era Revolusi Industri 4.0 - Lisnawati, Dewi (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
Pesantren is one of the oldest educational institutions in Indonesia that has better capabilities than other educational institutions in terms of character building. Based on the results of previous studies explained that the students have some strong positive characters and weak positive characters. Five strong positive characters in the students themselves are gratitude, fairness, citizenship, kindness and hope. While weak positive characters include self regulation, bravery, creativity, perspective, and humor. Some of these weak positive characters if related to the four 21st century skills competencies, these weak positive characters can be challenges and obstacles of students in the industrial revolution era 4.0. To answer these challenges the pesantren especially the traditional pesantren must start responding actively through curriculum renewal and learning methods, but without eliminating the culture, values ​​and characteristics of the traditional pesantren.